Superradiation of classical oscillators at constant pumping - Poklonskiy, E.V.; Totkal, S.O. (Problems of Atomic Science and Technology, 2022)
The dependence of the generation efficiency in the superradiance regime of an ensemble of oscillators on the pump energy input rate, as well as on the characteristics of the change in the pump phase, is studied. It is assumed that the pumping phase can vary both in time and in space. The most efficient pumping method remains the mode with slow energy input into the system, in comparison with the characteristic generation time, and the nature of the distribution of the field phase along the system can be either random or with a certain spatial period, but slightly changing with time. Досліджено залежність ефективності генерації в режимі надвипромінювання ансамблю осциляторів від швидкості введення енергії накачування, а також від характеристик зміни фази накачування. Передбачається, що фаза накачування може змінюватися як від часу, так і в просторі. Найбільш ефективним способом накачування залишається режим з повільним введенням енергії в систему, порівняно з характерним часом генерації, причому характер розподілу фази поля вздовж системи може бути як випадковим, так і з певним просторовим періодом, що змінюється з часом.